Product Performance Quality and Brand Awareness on Consumer Satisfaction: Pengaruh kualitas kinerja produk dan kesadaran merek terhadap kepuasan konsumen produk indachi prima di jawa barat - Ramadani, Dendi; Setiawan, Rahyuniati; Lindayani (Li Falah: Journal of Islamic Economics and Business, 2025)
The purpose of this study is to analyze how Product Performance Quality and Brand Awareness of Indachi Prima products in West Java influence customer satisfaction. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the study applies quantitative techniques with a saturated sampling approach to test the relationships between these factors. The results indicate that brand awareness has a significant influence on customer satisfaction (p = 0.000), while product performance quality also significantly affects customer satisfaction, albeit to a lesser degree (p = 0.000). This model demonstrates good data consistency, with both factors playing important roles in shaping consumer satisfaction. The findings suggest that, while both product performance quality and brand awareness are beneficial to consumers, brand awareness has a stronger influence on customer satisfaction than product performance quality. Based on these results, businesses, particularly in the textile industry, should prioritize enhancing brand awareness through targeted marketing campaigns, social media engagement, and strategic partnerships to increase customer satisfaction and loyalty. This study contributes to the existing literature by providing empirical evidence on the relative importance of brand awareness and product performance quality in influencing customer satisfaction, offering practical insights for companies looking to improve their market positioning through effective brand management strategies.